1998
DOI: 10.1021/ja981597+
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Oxidation of 2‘-Deoxyguanosine by Mn-TMPyP/KHSO5 to Imidazolone dIz without Formation of 8-Oxo-dG

Abstract: Oxidation of 2‘-deoxyguanosine dG with the chemical nuclease Mn-TMPyP/KHSO5 leads within one minute to a nearly quantitative amount of 2-amino-5-[(2-deoxy-β-d-erythro-pentofuranosyl)amino]-4H-imidazol-4-one (dIz or imidazolone for short) (90%) in a non-oxygen-dependent pathway and without formation of 8-oxo-dG. This new mechanism of dIz formation involves, as a crucial first step, the abstraction of two electrons from guanine by a high-valent porphyrin−Mn(V)O species, leading to the dG+ cation instead of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(135 citation statements)
references
References 36 publications
8
125
0
2
Order By: Relevance
“…This involves the opening of the pyrimidine at the C5-C6 bond with subsequent decarboxylation that is accompanied by hydration of the 7,8 double bond. Then, the carbinolamine thus generated, is likely to undergo ring-chain tautomerism that leads to opening of the imidazole ring with the release of formylamine [19]. Subsequent intramolecular cyclization of the guanidine substituent of the resulting intermediate would give rise to Iz.…”
Section: One-electron Oxidation Reactionsmentioning
confidence: 99%
“…This involves the opening of the pyrimidine at the C5-C6 bond with subsequent decarboxylation that is accompanied by hydration of the 7,8 double bond. Then, the carbinolamine thus generated, is likely to undergo ring-chain tautomerism that leads to opening of the imidazole ring with the release of formylamine [19]. Subsequent intramolecular cyclization of the guanidine substituent of the resulting intermediate would give rise to Iz.…”
Section: One-electron Oxidation Reactionsmentioning
confidence: 99%
“…That is the reason why Abs at the irradiation wavelength decreased exponentially with time. I t abs can be expressed by: (3) where I 0 is the incident energy (in J s -1 ) and k is the photodegradation rate constant (in s -1 ) obtained from the slope of a plot of In (A 0 /A t ) versus the elapsed time in seconds.…”
Section: Dyementioning
confidence: 99%
“…They are capable of catalyzing a wide range of oxidation reactions: from hydroxylation of alkanes and epoxidation of alkenes to drug oxidation and DNA cleavage. [1][2][3] More recently, porphyrins have attracted even more attention from researchers in various fields due to their phototherapeutic properties. [4][5][6] Photodynamic therapy (PDT) is a form of neoplastic diseases treatment using a photosensitizer, oxygen and light.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, HOCl is a strong two-electron oxidant, having an E°Ј of ϩ1.08 V, and might oxidize guanosine, resulting in guanosine ϩ via a two-electron oxidation. However, it has been reported that 8-oxo-dGuo is not formed from 2Ј-deoxyguanosine by another two-electron oxidant, an artificial nuclease MnTMPyP/KHSO 5 (34). On the basis of these biophysical data, we propose that 8-oxo-(d)Guo formation by HOCl is not mediated by a two-electron oxidation reaction but can be mediated through formation of an N-7 chlorine adduct cation from guanosine and Cl ϩ and a further reaction with H 2 O (Fig.…”
Section: Table I Effect Of Ferrous and Ferric Ions On Hocl-mediated Fmentioning
confidence: 99%